Shareholder Preferences and Dividend Policy. - Brennan, Michael J; Thakor, Anjan V (Journal of Finance, 1990)
This paper develops a theory of choice among alternative procedures for distributing cash from corporations to shareholders. Despite the preferential tax treatment of capital gains for individual investors, it is shown that a majority of a firm's shareholders may support a dividend payment for small distributions. For larger distributions, an open-market stock repurchase is likely to be preferred by a majority of shareholders and, for the largest distributions, tender offer repurchases dominate.